Menganalisis hubungan dan implikasi nilai-nilai karakteristik dalam kompetensi inti - Warih Zunu Pamungkas; Yuliana Dwi Hapsari (Reflection : Islamic Education Journal, 2024)
The aim of this research is to analyze the relationship and influence of character values ​​on Main Competencies (KI), Main Competencies (KD), Learning Outcomes (CP), Competency Achievement Indicators (GPA) and Learning Objectives in the Islamic context. Religious education . The literature research method with the topic "Analysis of the relationship and influence of character values ​​on core competencies" includes data collection through library research, a qualitative approach, data analysis and method validation by referring to a pre-existing framework. . study. This research reveals that: 1) CD is a student's learning outcome, KI is the most important skill in social life, KP is what is expected of students, and competency indicators are an assessment of CD, all of which are important for achieving learning. targets, 2) core competencies. and competency foundation as a foundation and teachers who understand well KI, CD and indicators of effective learning planning and in accordance with learning objectives, CD, AP, GPA and learning objectives that focus on positive values ​​such as honesty, discipline, cooperation, responsibility , appreciate diversity, creativity, discipline, appreciate and desire to create individuals who are ethical and competent in facing life's challenges, 4) Exemplary good and correct CD, KI, CP, GPA. The aim of this research is that understanding and applying character values ​​to core competencies can help form more competent and ethical individuals in society.